2020
DOI: 10.1155/2020/1891285
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Home Overnight Pulse Oximetry in Patients with Suspected Sleep-Disordered Breathing

Abstract: Background and Objective. To determine the diagnostic yield of nocturnal oximetry versus polygraphy for the diagnosis and classification of sleep apnea hypopnea syndrome (SAHS). Methods. Prospective study conducted in a university hospital. Subjects with a clinical suspicion of SAHS were included. All of them underwent home polygraphy and oximetry on the same night. A correlation was made between the apnea-hypopnea index (AHI) and the oximetry variables. The variable with the highest diagnostic value was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Other studies have identified similar values for specificity, but reported the sensitivities of 42.0% ( 14) and 80.0% (15) for detecting mild apnea using ODI (compared to PSG type I). For moderate apnea, we found the same sensitivity as that for mild apnea (66.7%); however, specificity was slightly lower (85.3%) and in an intermediate range compared to the reports in the literature (69.1 to 95.1%) (14,15,20,26,29). For severe apnea, ODI sensitivity was 95.5% and specificity was 88.9%, similar to previously reported studies (14,15,20,29).…”
Section: ' Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Other studies have identified similar values for specificity, but reported the sensitivities of 42.0% ( 14) and 80.0% (15) for detecting mild apnea using ODI (compared to PSG type I). For moderate apnea, we found the same sensitivity as that for mild apnea (66.7%); however, specificity was slightly lower (85.3%) and in an intermediate range compared to the reports in the literature (69.1 to 95.1%) (14,15,20,26,29). For severe apnea, ODI sensitivity was 95.5% and specificity was 88.9%, similar to previously reported studies (14,15,20,29).…”
Section: ' Discussionsupporting
confidence: 87%
“…For moderate apnea, we found the same sensitivity as that for mild apnea (66.7%); however, specificity was slightly lower (85.3%) and in an intermediate range compared to the reports in the literature (69.1 to 95.1%) (14,15,20,26,29). For severe apnea, ODI sensitivity was 95.5% and specificity was 88.9%, similar to previously reported studies (14,15,20,29). Evaluation of the degree of correlation to explain the variability of ODI in relation to that of AHI revealed an r of 0.93 and R 2 of 86.17% (po0.05).…”
Section: ' Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The best cutoff for ODI to predict moderate-to-severe and severe sleep apnea was chosen by comparing the predictive parameters of 3 commonly used ODI cutoffs (ODI ≥5, ODI ≥10, and ODI ≥15 events/h) reported in the literature. 24,25 Sensitivity of at least 70% was considered adequate to maximize the predictive performance. High sensitivity was prioritized over specificity, because in clinical setting, it will enable identification of most patients with sleep apnea.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%